OXIDATIVE STRESS AND ALTERED LEVELS OF OXIDANTS AND ANTIOXIDANTS IN ACUTE ISCHEMIC STROKE PATIENTS IN A REGION OF EAST TURKEY - Ozbey, Ulku; Seyran, Ayse; Erisir, Mine; Ozel, Seda; Berilgen, M. Said (John Wiley & Sons Inc, 2009)
[Abstract Not Available]